Dialectal variation by learners of Spanish in an immersion setting abroad: A quantitative analysis of leísta use in spoken and written discourses - Salgado-Robles, Francisco (Lenguas Modernas, 2015)
In the last two decades numerous studies have been conducted to document the linguistic advantages of study abroad (SA) experiences on the acquisition of a second language (L2). After an extensive research on the L2 outcomes of Spanish immersion programs, some questions pertaining to the acquisition of patterns of language variation common to a particular community in a study abroad context remain unanswered. This article explores the degree to which a group of learners of Spanish acquire the dialectal variation of leísmo after participating in a four-month SA immersion program in Valladolid (Spain). A quantitative analysis examinesthis linguistic phenomenon in two types of discourse: oral and written. The results suggest that SA learners do develop an awareness of non-standard forms of the targetlanguage, which are incorporated primarily into their oral language repertoire. In sum, this study contributes to add further knowledge about the developmentof sociolinguistic competence after a sojourn abroad, and to fill a gap in the new strand of studies on the acquisition of dialectal variation.